2019
DOI: 10.1002/pa.1876
|View full text |Cite
|
Sign up to set email alerts
|

Food security and access to healthy foods in Indian country: Learning from the Food Distribution Program on Indian Reservations

Abstract: Food access, food security, and nutrition‐related health disparities have long been recognized as particular challenges for Native Americans living on tribal land. The U.S. Department of Agriculture (USDA) provides nutrition assistance to tribal communities through the Food Distribution Program on Indian Reservations (FDPIR). In 2016, we completed a study of the FDPIR program for USDA's Food and Nutrition Service. This was the first national update since 1990. We found that FDPIR continued to serve people of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…The effect of multiple disadvantages—being AI/AN, living in neighborhoods with more food insecure households, in CHSDA counties—may put these individuals at even higher risk for COVID-19 infection. CHSDA counties may have greater residential segregation between AI/ANs and White-nHs [ 15 ], where AI/ANs may be more likely to live on or very close to reservations with higher levels of food insecurity [ 48 ], while White-nHs may live in separate, less food-insecure communities. Moreover, previous research found that AI/ANs living on reservations must travel further to grocery stores compared to other low-income individuals nationally [ 49 ], which may suggest fewer grocery stores and other food resources in rural communities on or near reservations.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of multiple disadvantages—being AI/AN, living in neighborhoods with more food insecure households, in CHSDA counties—may put these individuals at even higher risk for COVID-19 infection. CHSDA counties may have greater residential segregation between AI/ANs and White-nHs [ 15 ], where AI/ANs may be more likely to live on or very close to reservations with higher levels of food insecurity [ 48 ], while White-nHs may live in separate, less food-insecure communities. Moreover, previous research found that AI/ANs living on reservations must travel further to grocery stores compared to other low-income individuals nationally [ 49 ], which may suggest fewer grocery stores and other food resources in rural communities on or near reservations.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that recent efforts to improve fresh fruit and vegetable offerings and culturally relevant foods in FDPIR ( Mucioki et al, 2018 ) might increase dietary fiber intake among recipients. It should also be noted that FDPIR offers nutrition education through partnerships, grants, and direct programming that includes gardening, cooking classes, youth engagement, and a variety of other activities aimed at addressing a range of diet- and health behaviors ( Pindus and Hafford, 2019 ), which could also impact dietary fiber consumption.…”
Section: Discussionmentioning
confidence: 99%
“…hunting, fishing, and gathering) and increased reliance on industrialized food systems ( Settee and Shukla, 2020 ). Numerous studies have documented barriers to healthy food access, quality, and affordability on federal Indian reservations, as well as high rates of food insecurity, one of many symptoms of settler colonialism and systemic racism in contemporary food systems ( Byker Shanks et al, 2019 , Chodur et al, 2016 , Fretts et al, 2018 , Jernigan et al, 2017 , Jernigan et al, 2012 , Kaufman et al, 2014 , Mucioki et al, 2018 , Pindus and Hafford, 2019 , Wetherill et al, 2018 ). A 2012 US Department of Agriculture (USDA) report found that 23% of Native American households were food insecure, compared to 15% of all US households ( Gordon and Oddo, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that while major U.S. philanthropic organizations focus on improving healthcare in economically disadvantaged parts of the world, the healthcare available to their domestic poor is frequently overlooked [14]. The fact that Native American Reservations are a recognized "food desert" without access to staple essentials such as fresh produce is often ignored [15,16]. In global food studies, diabetes is a recognized epidemic among the poor in emerging and developing countries.…”
Section: Global Issue Recognitionmentioning
confidence: 99%